Application of urine C-peptide creatinine ratio in type 2 diabetic patients with different levels of renal function - Zhou, Wan; Li, Jie; Yuan, Xiaojing; Wang, Wei; Zhou, Huanran; Zhang, Haoqiang; Ye, Shandong (Frontiers in Endocrinology, 2022)
Abstract Objective This study aims to investigate the effect of single urine C peptide / creatinine (UCPCR) in assessing the islet β Cell function of type 2 diabetes mellitus (T2DM) patients with different renal function. Methods A total of 85 T2DM patients were recruited in this study, all the patients were assigned to one group with estimated glomerular filtration rate (eGFR)≤60 ml•min-1•1.73 m-2 and another group complicated with eGFR>60 ml•min-1•1.73 m-2. Serum creatinine, urine creatinine, serum fasting C-peptide (FCP), fasting blood glucose (FBG), glycosylated hemoglobin (HbA1C) and 24-hour urinary C-peptide (24hUCP) were measured. The modified homeostasis model assessment-islet β cell function [HOMA-islet (CP-DM)], the modified homeostasis model assessment-insulin resistance [HOMA-IR(CP)] and UCPCR were calculated. Results When compared with group eGFR <60 ml•min-1•1.73 m-2, the levels of UCPCR, FCP, the modified HOMA-IR(CP) and HOMA-islet (CP-DM) were promoted and the concentrations of HbA1C, FPG, creatinine were decreased in the patients of eGFR>60 ml•min-1•1.73 m-2 (P＜0.05); FCP was uncorrelated with 24hUCP while associated with UCPCR in the patients of eGFR≤60 ml•min-1•1.73 m-2; UCPCR was positively correlated with FCP and HOMA-IR(CP) in the T2DM patients with different levels of renal function; the cut-off (UCPCR≤1.13 nmol/g) had 88.37% sensitivity and 95.24% specificity [95% confidence interval (CI):0.919-0.997] for identifying severe insulin deficiency in T2DM patients[area under the curve (AUC) 0.978]. Conclusion UCPCR can be used to evaluate islets β Cell function in T2DM patients with different renal function status.